8(6z+7y)-11(2y+8z)=0

Simple and best practice solution for 8(6z+7y)-11(2y+8z)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(6z+7y)-11(2y+8z)=0 equation:


Simplifying
8(6z + 7y) + -11(2y + 8z) = 0

Reorder the terms:
8(7y + 6z) + -11(2y + 8z) = 0
(7y * 8 + 6z * 8) + -11(2y + 8z) = 0
(56y + 48z) + -11(2y + 8z) = 0
56y + 48z + (2y * -11 + 8z * -11) = 0
56y + 48z + (-22y + -88z) = 0

Reorder the terms:
56y + -22y + 48z + -88z = 0

Combine like terms: 56y + -22y = 34y
34y + 48z + -88z = 0

Combine like terms: 48z + -88z = -40z
34y + -40z = 0

Solving
34y + -40z = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '40z' to each side of the equation.
34y + -40z + 40z = 0 + 40z

Combine like terms: -40z + 40z = 0
34y + 0 = 0 + 40z
34y = 0 + 40z
Remove the zero:
34y = 40z

Divide each side by '34'.
y = 1.176470588z

Simplifying
y = 1.176470588z

See similar equations:

| -x-14=-3x+14 | | x^2+25-6=0 | | 50x^4-8=0 | | 3.6+8= | | 131-2x=34x+19 | | x^2+5x+6x=0 | | 2i-2y=17 | | 4.5+2= | | -7x-10=12-9x | | x^3+12x^2-27x= | | x=-y+6 | | -62-7x=91-28x | | 5x+15+6x-5=360 | | 5x+15+6x-5=180 | | 500-4x= | | 4x+4=2e-11 | | -3t^2+28t=0 | | -s^2+9s=0 | | 9x^3-3x^3-3x+1=0 | | 2i-y=14 | | 78+r=-8 | | 6x-5+5x+15=180 | | 7x=4x+74 | | -x-184=8x+77 | | 3x^2+34x+115=0 | | y=2x^3-6x^2-20x | | Tn=3n+7 | | -5-5a+5= | | x+y=zfory | | 200=24+(n-1)11 | | 17-6-20y=8(3y-1) | | 12e-2=26 |

Equations solver categories